Correlation of serum anti-mullerian hormone levels with serum follicular stimulating hormone, luteinizing hormone and testosterone levels in male patients of depression - Nasar Abbas Shamsi; Shazadi Ambreen; Hira Ayaz (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the correlation of serum anti-mullerian hormone with follicular stimulating hormone, luteinizing hormone and testosterone levels in male patients of depression. Method: The cross-sectional analytical study was conducted at the Islamic International Medical College and the Armed Forces Institute of Mental Health, Military Hospital, Rawalpindi, Pakistan, from March 4, 2017, to March 29, 2018, and comprised male patients aged 18-60 years suffering from depression diagnosed on the basis of Siddiqui Shah Depression Scale. Serum anti-mullerian hormone, follicular stimulating hormone, luteinizing hormone and testosterone levels of all patients were measured using enzyme-linked immunosorbent assay kits. Correlation of anti-mullerian hormone with the rest was explored. Data was analysed using SPSS 21. Results: There were 72 male subjects with mean age 35.19±9.97 years. A significant negative correlation was observed between serum anti-mullerian hormone levels and serum follicular stimulating hormone levels (p=0.001), but the correlation was not significant with serum luteinizing hormone and serum testosterone levels (p>0.05). Conclusion: Anti-Mullerian Hormone was found to be significantly correlated with follicular stimulating hormone, but not with luteinizing hormone and testosterone. Key Words: Depression, Testosterone, Anti-mullerian hormone.